World Bank Country-Level Engagement on Governance and Anticorruotion : An Evaluation of the 2007 Strategy and Implementation Plan - Independent Evaluation Group (Washington, DC: World Bank Group, 2013)
Well-governed countries is better able to formulate growth-enhancing policies, deliver essential services to the poor, and regulate financial and product markets. The appeal of governance reform and the fight against corruption can resonate widely across diverse countries and social groups, as demonstrated by recent events in the Middle East and North Africa. Building on more than two decades of experience, the World Bank's 2007 governance and anticorruption (GAC) strategy reaffirmed its continuing commitment to the crucial and challenging agenda of helping countries develop accountable and effective states. Focusing on the country operational aspects of the overall GAC agenda, the Independent Evaluation Group (lEG) assessed the relevance and effectiveness of the strategy and its first phase of implementation efforts over fiscal years 2008-10. A key feature of the evaluation is its benchmarking of the content and quality of the Bank's country-level engagement on GAC issues, before and after the 2007 strategy. The findings of this evaluation are, by design, intended to inform a planned second phase of the GAC implementation, a learning process that signals one of the Bank's strengths. They can be viewed in the context of an ongoing change management and internal reforms agenda, which includes the strengthening of the Integrity Vice Presidency, a new World Bank Institute strategy, an institution-wide transparency initiative, and efforts to modernize investment lending.